2014
DOI: 10.1111/ajt.12858
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of the Cellular and EBV-Specific MicroRNAome in Primary CNS PTLD Identifies Different Patterns Among EBV-Associated Tumors

Abstract: Primary central nervous system (pCNS) posttransplant lymphoproliferative disorder (PTLD) is a complication of solid organ transplantation characterized by poor outcome. In contrast to systemic PTLD, Epstein-Barr virus (EBV)-association of pCNS PTLD is almost universal, yet viral and cellular data are limited. To identify differences in the pattern of EBV-association of pCNS and systemic PTLD, we analyzed the expression of latent and lytic EBV transcripts and the viral and cellular microRNAome in nine pCNS (eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
3
39
0
Order By: Relevance
“…Some Hodgkin’s and non-Hodgkin’s B-cell neoplasms are considered “EBV-associated” based on detection of EBV-encoded RNA in tumor tissue by in situ hybridization (EBER-ISH) 3,4 . Over 90% of PCNS-PTLD cases show EBV-association by immunohistochemistry 5 . Patients with acquired, iatrogenic, or congenital immunodeficiency are at increased risk of developing an EBV associated B-cell neoplasm 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Hodgkin’s and non-Hodgkin’s B-cell neoplasms are considered “EBV-associated” based on detection of EBV-encoded RNA in tumor tissue by in situ hybridization (EBER-ISH) 3,4 . Over 90% of PCNS-PTLD cases show EBV-association by immunohistochemistry 5 . Patients with acquired, iatrogenic, or congenital immunodeficiency are at increased risk of developing an EBV associated B-cell neoplasm 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Antiviral therapy targeting lytic gene expression is shown to be an effective treatment in some EBV-associated neoplasms 19 with in vitro data showing the additive induction of apoptosis in EBV+ cell lines treated with AZT and GCV 20,21 . Furthermore, constitutively active lytic-phase gene expression has been demonstrated in EBV+ PCNS-PTLD and systemic PTLDs 5,22,23 , raising the potential for antiviral therapy as an effective therapeutic option. Roychowdhury and colleagues demonstrated the effectiveness of AZT and GCV plus WBRT in preclinical models of EBV+ PCNS-PTLD and report a patient successfully treated with AZT and GCV without radiation 22 .…”
Section: Introductionmentioning
confidence: 99%
“…By detecting the EBV and cellular microRNAome in PTLD (Forte et al, 2012; Harris-Arnold et al, 2015), studies showed that there are two different microRNA profiles identified in primary central nervous system post-transplant lymphoproliferative disorders (pCNS PTLD). First, EBV microRNAs interacts with the cellular microRNAome similarly to that of EBV-associated systemic PTLD and the second could be limited to the immunological functions associated with the central nervous system (Moscato et al, 2013; Fink et al, 2014). Although, a limited expression of latency genes is also seen in EBV associated systemic PTLD, based on promoter utilization it is still considered to be latency III (Fink et al, 2014).…”
Section: Ebv Associated Diseasesmentioning
confidence: 99%
“…First, EBV microRNAs interacts with the cellular microRNAome similarly to that of EBV-associated systemic PTLD and the second could be limited to the immunological functions associated with the central nervous system (Moscato et al, 2013; Fink et al, 2014). Although, a limited expression of latency genes is also seen in EBV associated systemic PTLD, based on promoter utilization it is still considered to be latency III (Fink et al, 2014). A higher frequency of EBV in pCNS PTLD compared to systematic PTLD may result in pathological differences (Cavaliere et al, 2010).…”
Section: Ebv Associated Diseasesmentioning
confidence: 99%
“…BHRF1 miRNA suppresses expression of CXCL-11, an interferon-inducible chemokine and T cell attractant, which contributes to evasion of EBV-infected tumor cells by immunosurveillance of the host [26]. BART miRNA are expressed in each state of latency, and BART miRNA and BHRF1 are expressed in all EBV-positive PTLD [27], suggesting a significant role of the viral miRNAs of EBV in the etiology of EBV-positive lymphomas.…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%